Managing the Archaeological Records: Present Practices and Future Trends - Al-Belushi, Mohammed Ali (Journal of Humanities & Social Sciences, 2023)
Archaeological data records represent the primary and most important source of information related to the management of various components of the historical environment. Due to this importance, in recent decades, archaeological authorities in some countries have developed numerous databases. This paper examines the history, evolution, and role of archaeological databases in the preservation and management of heritage resources. It provides a review of the types of archaeological databases and their uses as important sources of information for management, research, education, and planning systems. The paper also highlights current practices and future trends in the documentation of archaeological heritage components. The study adopts a descriptive approach based on surveying and reviewing published literature on archaeological data records in several countries worldwide. The study concludes that there has been a rapid development in the techniques used to document various elements of archaeological heritage. While some countries now possess advanced records, a significant number of countries are still in the early stages of recording their archaeological resources. The study recommends that archaeological authorities give significant importance to archaeological databases and their development in line with emerging computing technologies. They should be designed to meet the new requirements of different user groups and integrated into development plans and projects that may directly or indirectly affect the archaeological heritage.ll, manuscripts must include Abstracts in English and Arabic (with identical information) of (150 to 250) words, and the language used in it must be scientific, precise, and free of spelling mistakes.